A naturalistic 1 year follow-up study of the elderly patients with depression visiting the psychiatric outpatient services for the first time. (September 2018) - Grover, Sandeep; Mehra, Aseem; Dalla, Eish; Chakrabarti, Subho; Avasthi, Ajit
Highlights: 41.4% of elderly patients with depression did not return to the clinic after the first visit. Majority of the patients who continued to follow-up at 6 month and 1 year continued to take the prescribed medications. 75% and 90% patients dropped out from the clinic by 6 months and 1 year. 65% of patients achieved improvement in symptoms to the extent of 81–100%. Abstract: This naturalistic study aimed to assess treatment dropout pattern, course of symptoms and outcome of depression among the elderly. This study aimed to assess the course and outcome of depression and treatment dropout pattern of patients with depression in old age. Additionally an attempt was made to study the predictors of outcome and dropout. 140 elderly patients (≥ 60 years) were followed up at 6 months and 1 year to evaluate the status of their depression and treatment pattern. Out of the 140 patients recruited at the baseline, 58 (41.4%) patients did not return to the clinic after the first visit. 65.7%, 75% and 90% patients dropped out from the clinic by 3 months, 6 months and 1 year after registration with the clinic. At 1 year, about two-third (65%) of patients achieved improvement in symptoms to the extent of 81–100% and only 10% did not show any improvement throughout the study period. To conclude present study suggests that large proportion of the elderly patients with depression attending a mental health service dropout of treatment. Despite the high dropouts rate, more than three-fourth of the patients improve to the extent of 81–100% and very few patients have worsening of symptoms or persistent symptoms.